A Comprehensive Clinicopathological Analysis of the First Wave of COVID-19 in Slovakia - Lucia Krivosikova; Michal Palkovic; Pavol Janega; Kristina Mikus Kuracinova; Andrea Janegova; Pavel Babal (COVID)
The early introduction of strict measures during the first wave of COVID-19 in Slovakia resulted in a low number of fatal cases. Most of them (27/28) were autopsied with microscopic evaluation focusing on changes in the lungs. The average age of the patients was 79. The most common microscopic finding was diffuse alveolar damage in various stages. There were statistically significant relationships between microthrombi and neutrophil count, level of C-reactive protein, and immobility. Oxygen therapy, as a factor that might cause changes typical for diffuse alveolar damage, showed statistically significant relationships with perivascular lymphocytic infiltrate, alveolar capillaritis, alveolar bleeding, and pneumocyte hyperplasia. Hyaline membranes showed a statistically significant relationship with monocyte count, and borderline statistically significant relationships with platelet count and antimalarial therapy. The level of C-reactive protein and neutrophil count seemed to be useful for predicting microthrombi formation. Interestingly, there were no statistically significant relationships between microthrombosis and anticoagulant therapy, platelet count, or level of D-dimer.